Pholiota oblita, new species in sect. Adiposae stirps Subflammans (Strophariaceae, Agaricomycetes), from the Argentinean Yungas - Niveiro, Nicolás; Popoff, Orlando F.; Lechner, Bernardo E.; Albertó, Edgardo O. (Phytotaxa, 2014)
We present a study on the genus Pholiota sect. Adiposae stirps Subflammans from the Republic of Argentina. Pholiota oblita is proposed as a new species. It is characterized by its narrow lamellae, elongated cheilocystidia and broad spores. Singer originally described this species as P. digilioi, but this name was never validly published. Pholiota oblita is close to P. flammans, from the Northern Hemisphere, and P. subflammans, from the South American Andino-Patagonic forest, but differs by the diagnostic characters previously mentioned. The species was found in the southern end of the Yungas Forest, a cloud forest located on the eastern slopes of the sub-Andean mountains. Numerous collections of P. oblita were found in the Yungas forest but not in other areas. We believe that it could be an endemic species. Furthermore, we found that there are no herbarium specimens for the type of Pholiota subflammans (Speg.) Sacc. With the absence of original material, and to preserve current usage of the name, a neotype is designated hereby. The neotype chosen for P. subflammans is a specimen determined, described, and collected by Singer in the same area where the type specimen was found by Spegazzini.